2008
DOI: 10.5483/bmbrep.2008.41.10.733
|View full text |Cite
|
Sign up to set email alerts
|

TC1 (C8orf4) is involved in ERK1/2 pathway-regulated G1- to S-phase transition

Abstract: Although previous studies have implicated a role for TC1 (C8orf4) in cancer cell proliferation, the molecular mechanism of its action is still largely unclear. In this study, we showed, for the first time, that the mRNA levels of TC1 were upregulated by mitogens (FBS/thrombin) and at least partially, through the ERK1/2 signaling pathway. Interestingly, the over-expression of TC1 promoted the G1-to S-phase transition of the cell cycle, which was delayed by the deficiency of ERK1/2 signaling in fibroblast cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In addition, PROX1 regulates several genes that were previously associated with thyroid cancer. For example, Thyroid Cancer (TC)-1 was originally isolated by its prominent expression in thyroid cancer cells (24,25) and known to promote G1/S cell cycle progression (26). While TC-1 was upregulated in PTCs, it was significantly downregulated by PROX1 re-expression (Figure 4E,F).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PROX1 regulates several genes that were previously associated with thyroid cancer. For example, Thyroid Cancer (TC)-1 was originally isolated by its prominent expression in thyroid cancer cells (24,25) and known to promote G1/S cell cycle progression (26). While TC-1 was upregulated in PTCs, it was significantly downregulated by PROX1 re-expression (Figure 4E,F).…”
Section: Resultsmentioning
confidence: 99%
“…TC-1 is thought to competitively block interactions between β-catenin and a repressor protein, leading to upregulation of β-catenin target genes [39]. TC-1 may also play a role in NF-κB and ERK signaling pathways [40]. Downregulation TC-1 can thus lead to aberrant signaling, causing disrupted embryonic development or carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…A study performed with A549 lung adenocarcinoma cell line exposed to hyperoxia (95% O 2 ) for 0.5–24 h demonstrated that suppression of phospho‐ERK activity by U0126 MEK inhibitor resulted in downregulation of cyclinA/B1 levels and increased the cell fraction in S phase 6. At the same time, the reduced activity of phospho‐ERK in fibroblasts results in downregulation of cyclin D1 expression and enriches cells in G1 phase 33. These data suggest that the regulation of cyclins by phospho‐ERK activity depends on the origin of the tissue.…”
Section: Discussionmentioning
confidence: 99%